2023
DOI: 10.1021/acs.energyfuels.3c02251
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Ignition and Flame Propagation of Ammonia/n-Heptane Dual Fuels

Wanhui Zhao,
Guiqiang Li,
Ting Sun
et al.

Abstract: Ammonia is carbon-free and thus is a promising renewable fuel for carbon neutrality. However, because ammonia has low reactivity and narrow flammability range, blended fuels of ammonia/n-heptane are often used to trigger high-temperature combustion in internal combustion engines. In this study, the ignition and flame propagation of ammonia/n-heptane dual-fuels were investigated in a specified mixing layer using a skeletal mechanism via a high-fidelity simulation. The results showed that auto-ignition was initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…It is observed that the LTHR appears earlier with the advance of injection timing, while the LTHR is hardly observed at SOI = −40 °CA aTDC. Such an observation is mainly ascribed to the spray mixing process and nonlinear correlations between NTC chemistry and thermodynamic conditions. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the LTHR appears earlier with the advance of injection timing, while the LTHR is hardly observed at SOI = −40 °CA aTDC. Such an observation is mainly ascribed to the spray mixing process and nonlinear correlations between NTC chemistry and thermodynamic conditions. , …”
Section: Resultsmentioning
confidence: 99%
“…Such an observation is mainly ascribed to the spray mixing process and nonlinear correlations between NTC chemistry and thermodynamic conditions. 33,34 Figure 3B presents the pressure histories and AHRR for different n-heptane energy ratios at SOI = −50 °CA aTDC. Similar to Figure 3A, the n-heptane energy ratio significantly influences combustion processes.…”
Section: Pressure-based Combustion Characteristicsmentioning
confidence: 99%
“…Although NH 3 has many benefits, several obstacles need to be addressed before NH 3 can be applied in combustion equipment (e.g., spark ignition (SI) and compression ignition (CI) engines). These obstacles include high-autoignition temperature, , minimum ignition energy, low flame propagation speed, , narrow flammability range, and toxicity . Taking the NH 3 application in the CI engine as an example, it requires a higher compression ratio than that of conventional transport fuel to maintain stable operation.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia serves as a refrigerant in large industrial refrigerators and is a key component of fertilizers and various industrial goods. In recent years, ammonia has been considered as a potential alternative fuel and hydrogen storage carrier in power systems and energy storage due to its carbon-free nature and high hydrogen density. Due to its excellent thermal properties, ammonia is well suited for large-scale storage and transportation. , In addition, ammonia is a highly toxic chemical that can cause environmental pollution and injury if accidentally burned or exploded. The lower molecular weight of ammonia allows for faster diffusion compared with ambient air. During the storage, transport and bunkering of ammonia as well as hydrogen production during ammonia cracking, ammonia leakage in the high-pressure storage containers and hitting ignition sources can lead to explosions, structural damage to buildings, and destruction of production facilities, endangering personal safety .…”
Section: Introductionmentioning
confidence: 99%